KONSUMSI YOGHURT DAN PERSEPSI PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS SUMATERA UTARA TAHUN ANGKATAN 2012-2015 - Fattia Ramadhani; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
To keep maintance body health, it must keep the amount of non pathogenic bacteria in the gut in order to stay balanced. The increasing number of bacteria in the gut, it will boost immunity to the disease. It caused by the good bacteria that stimulate various factors prophylactic. Eating yoghurt is one effort in keeping it healty digestion. Yoghurt is one of functional food which fermented from milk by Using Lactic Acid Bacteria (LAB). Presence of Lactic Acid Bacteria in yoghurt provides a lot of benefits for health, which are rich in nutrients, increase the body’s immune response, maintain intestinal health, and etc. The purpose of this study was to analyze the concumption and perception of yoghurt drink on student. The study was conducted to faculty of public health in University student of North Sumatera years generation 2012-2015. The research’s type used is descriptive with device of cross study sectional. The total samples were 96 students. Data collection methods include primary data are respondence characteristic of student (age, gender, pocket money), reseources, knowledge, perception, and consumption of yoghurt by using questionnaires, and secondary data collected from the data of the faculty of public health include population numbers and description of the faculty concerned. The results showed that Students who have a good knowledge derived mostly from friends and family. Result of research Students who have a good knowledge mostly have a good perception of yoghurt also is equal 90,3%. This study also showed that Student who have a good perception mostly have a good frekuensi of yoghurt is equal 50,0%. And The results showed that Student who have pocket money Rp40000-Rp50000 mostly yoghurt drink consumption frequency for one week. Based on the result of research suggested to student faculty of public health. to increase the frequency of yoghurt consumption, because consuming yoghurt regularly is able to give some positive effect for human’s health. Keywords : Consumption, Perception, Yoghurt, Student